1972
DOI: 10.1254/jjp.22.59
|View full text |Cite
|
Sign up to set email alerts
|

Contractile Responses of Spiral Strips of Large Blood Vessels From Rabbits to Transmural Stimulation and Tyramine

Abstract: Transmural electrical stimulation with repetitive pulses of short duration causes contrac tion of isolated vascular smooth muscles, which is suggested to correlate with excitation of adrenergic nerve terminals innervating the vascular wall (1,2). This is supported by findings which indicated that field stimulation causes contraction and an increased efflux of 3H-noradrenaline from rabbit main pulmonary arteries (3) and that a biologically active (gut relaxing) substance is released from stimulated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1972
1972
1981
1981

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…It has been suggested that contractions induced by transmural stimulation under conditions used in the present study result from nor adrenaline released by excitation of adrenergic nerves (9). Similar potentiation of re sponses to sympathetic nerve stimulation by angiotensin has been observed in isolated rabbit hearts (11), isolated rabbit portal veins and coeliac arteries (3), cat mesenteric blood vessels (5) and dog saphenous veins (12).…”
Section: Discussionsupporting
confidence: 76%
“…It has been suggested that contractions induced by transmural stimulation under conditions used in the present study result from nor adrenaline released by excitation of adrenergic nerves (9). Similar potentiation of re sponses to sympathetic nerve stimulation by angiotensin has been observed in isolated rabbit hearts (11), isolated rabbit portal veins and coeliac arteries (3), cat mesenteric blood vessels (5) and dog saphenous veins (12).…”
Section: Discussionsupporting
confidence: 76%
“…The method for stimulating intramural adrenergic nerves was the same as that described in an earlier report [13]. Square pulses of a 0.3-msec duration with supramaximum intensity (approximately 80 V [15]) at frequencies of 5 and 20/sec for 40 and 10 sec, respectively (thus total pulses applied being 200), were transmurally applied. Electrical pulses were provided by an electronic stimulator (type WSE-3R, Nihonkoden Kogyo).…”
Section: Methodsmentioning
confidence: 99%
“…The vascular strips were placed between a pair of stimulating electrodes (platinum plates, 5 x 15 mm), as described by Toda, Usui and Mori (23). The prepartions were transmurally stimulated by a train of 0.3 msec-rectangular pulses of supramaximal intensity (about 80 V) applied at frequencies of 5, 20 and 100/sec.…”
mentioning
confidence: 99%
“…The number of the electrical pulses was kept constant (200 pulses) by changing the period of stimulation (40, 10 and 2 sec for frequencies of 5, 20 and 100/sec, respectively). Contractile response to electrical stimulation applied under these conditions is shown to result from released noradrenaline (23). Electrical stimuli were provided by an electronic stimulator (Type WSE-3R, Nihon koden Kogyo Co.).…”
mentioning
confidence: 99%